The Action of D-Dopachrome Tautomerase as an Adipokine in Adipocyte Lipid Metabolism - Iwata, Takeo; Taniguchi, Hisaaki; Kuwajima, Masamichi; Taniguchi, Takako; Okuda, Yuko; Sukeno, Akiko; Ishimoto, Kyoko; Mizusawa, Noriko; Yoshimoto, Katsuhiko (PLOS ONE, 2012)
Adipose tissue is a critical exchange center for complex energy transactions involving triacylglycerol storage and release. It also has an active endocrine role, releasing various adipose-derived cytokines (adipokines) that participate in complex pathways to maintain metabolic and vascular health. Here, we found D-dopachrome tautomerase (DDT) as an adipokine secreted from human adipocytes by a proteomic approach. DDT mRNA levels in human adipocytes were negatively correlated with obesity-related clinical parameters such as BMI, and visceral and subcutaneous fat areas. Experiments using SGBS cells, a human preadipocyte cell line, revealed that DDT mRNA levels were increased in an adipocyte differentiation-dependent manner and DDT was secreted from adipocytes. In DDT knockdown adipocytes differentiated from SGBS cells that were infected with the adenovirus expressing shRNA against the DDT gene, mRNA levels of genes involved in both lipolysis and lipogenesis were slightly but significantly increased. Furthermore, we investigated AMP-activated protein kinase (AMPK) signaling, which phosphorylates and inactivates enzymes involved in lipid metabolism, including hormone-sensitive lipase (HSL) and acetyl-CoA carboxylase (ACC), in DDT knockdown adipocytes. The AMPK phosphorylation of HSL Ser-565 and ACC Ser-79 was inhibited in DDT knockdown cells and recovered in the cells treated with recombinant DDT (rDDT), suggesting that down-regulated DDT in adipocytes brings about a state of active lipid metabolism. Furthermore, administration of rDDT in db/db mice improved glucose intolerance and decreased serum free fatty acids levels. In the adipose tissue from rDDT-treated db/db mice, not only increased levels of HSL phosphorylated by AMPK, but also decreased levels of HSL phosphorylated by protein kinase A (PKA), which phosphorylates HSL to promote its activity, were observed. These results suggested that DDT acts on adipocytes to regulate lipid metabolism through AMPK and/or PKA pathway(s) and improves glucose intolerance caused by obesity.